Uji Stabilitas Fisik Formula Krim yang Mengandung Ekstrak Kacang Kedelai (Glycine max) - Dewi, Rosmala; Anwar, Effionora; KS, Yunita (UI Scholars Hub, 2014)
Soybean extract has known for its antiaging potential. The addition of soybean extract was predicted can influence the physical stability of the cream. Therefore, this research was aimed to test the physical stability of cream contained soybean extract in different concentration (2%, 4%, 6%, and 8%). The physical stability test including the storage for eight weeks at room temperature, high temperature (40°±2°C), and low temperature (4°±2°C). Stability parameters were the organoleptic observation, pH, globul size, viscosity, and cycling test. Those four cream formula showed good stability in organoleptic, pH, globul size, viscosity, and cycling test.